Swimming performance and larval quality are altered by rearing substrate at early life phases in white sturgeon, Acipenser transmontanus (Richardson, 1836). (December 2014) - Baker, D. W.; McAdam, D. S. O.; Boucher, M.; Huynh, K. T.; Brauner, C. J.
Summary To investigate the role of substrate enrichment on larval growth and performance, white sturgeon, Acipenser transmontanus, were reared for 12 dph (the pre‐feeding stage) in the presence and absence of enriched substrates (i.e. structurally complex media). Following this period, larval sturgeon were transferred to holding tanks with unenriched substrate (lacking structural complexity) and reared for an additional 30 days, during which time health and performance indicators (growth, Ucrit, startle response reaction time) and whole body lipid composition were assessed at 15 and 18°C. Sturgeon reared on unenriched substrates tended to grow more slowly (up to 40% reduced mass at 40 dph) with a lower condition factor (5–15% lower between 8 and 40 dph), but also exhibited delayed gut development and reduced rate of yolksac absorption (at 15 dph) than those reared with enriched substrates. Whole body lipid composition was significantly altered with substrate enrichment, although the biological relevance of these changes is unknown. White sturgeon reared without exposure to enriched substrates at some temperatures and developmental phases demonstrated modest reductions in aerobic ( 20–30% lower Ucrit) and startle response performance ( 5–10% slower reaction time) at 15 and 30 dph. Overall, most effects were influenced by rearing temperatures and parentage, such that differences were not statistically significant under all conditions. Clearly, however, substrate enrichment plays an important role in development of white sturgeon during early life stages.